2021
DOI: 10.1007/s00436-021-07089-9
|View full text |Cite
|
Sign up to set email alerts
|

Besnoitiosis in donkeys: an emerging parasitic disease of equids in Italy

Abstract: Besnoitiosis is an emerging parasitic disease of equids. Italy is one of the few European countries where the circulation of Besnoitia spp. antibodies was demonstrated. In this study, a case of clinical besnoitiosis in two donkeys in northern Italy is reported. The two animals were clinically examined. Serum and blood samples were analyzed for the detection of Besnoitia spp. antibodies and for hematology, biochemistry, and enzyme activity, respectively. ITS-1 PCR and sequencing were carried out on DNA extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Cysts were mainly present in the sclerae, conjunctivae, nares and muzzle in the two current cases, similar to previous reports where the sclera and the nares were the most common locations for Besnoitia lesions in donkeys [ 21 , 25 , 27 ]. No endoscopic examination was performed to look for the presence of laryngeal or nasopharyngeal cysts, which are less commonly identified [ 5 ], and vaginal mucosal cysts were not seen in the jenny here but had been identified in several cases previously [ 1 , 5 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Cysts were mainly present in the sclerae, conjunctivae, nares and muzzle in the two current cases, similar to previous reports where the sclera and the nares were the most common locations for Besnoitia lesions in donkeys [ 21 , 25 , 27 ]. No endoscopic examination was performed to look for the presence of laryngeal or nasopharyngeal cysts, which are less commonly identified [ 5 ], and vaginal mucosal cysts were not seen in the jenny here but had been identified in several cases previously [ 1 , 5 ].…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to other studies, where Besnoitia cysts were noted incidentally at post-mortem examination in donkeys that were euthanized for other reasons [ 23 , 28 ]. In contrast, single cases of equine besnoitiosis in South Africa [ 18 ], the USA [ 1 , 21 , 27 ], Belgium [ 24 ], and Italy [ 25 ] were reported as severely affected, demonstrating cachexia and/or debilitation. However, co-morbidities, such as significant burdens of endo- and ecto-parasites [ 25 ] were often found in these animals and were reflected in haematologic and biochemical alterations [ 1 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Elsheikha et al (2020) , the increasing number of reports in infections of B. bennetti in donkeys and other equids may be attributed to the improved awareness of the disease. Although infections in Africa has only been detected based on clinical signs, histological and pathological examination, exposure or infection of B. bennetti in equids in Europe were detected based on clinical signs, serological test (IFAT and western blot) ( Gutiérrez-Expósito et al, 2017 ) and partial rDNA sequencing ( Liénard et al, 2018 ), which have not been able to conclusively distinguish between species ( Villa et al, 2021 ). Schares et al (2021) isolated and identified B. darlingi -type naturally occurring in cheetah in Botswana based on conventional and real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reproductive failure might be one of the major concerns as males may develop infertility, sterility or even may die during the acute phase of the infection (Álvarez-García, Cortes et al, 2014;González-Barrio et al, 2020). Clinical besnoitiosis has also been described in other livestock species such as donkeys, goats and horses (Elsheikha et al, 2020;Liénard et al, 2018;Namazi et al, 2011;Villa et al, 2018Villa et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%